2018
DOI: 10.1108/ci-06-2017-0051
|View full text |Cite
|
Sign up to set email alerts
|

e-Tendering readiness in construction: the posterior model

Abstract: Purpose The purpose of this paper is to varied a conceptual model for e-Tendering readiness in any construction organisation prior of implementing e-Tendering system. Design/methodology/approach Based on conceptual model called e-Tendering readiness model (e-TRM), this paper empirically examines the e-TRM’s interactions and causal relationships between e-Tendering constructs and e-Tendering readiness. The paper uses the structural equation modelling technique to test the hypothesised positive inter-relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…For instance, the predictors could be used to develop an adoption index for safety technologies that practitioners can use as an empirical base for making informed decisions. Readiness index and adoption index have been explored using different methods with varying levels of success in other construction domains (Goodrum et al , 2011; Al Yahya et al , 2018). The authors are currently developing an adaptable adoption index for worker-centric safety technologies (wearable safety device for example) utilizing the findings of the present research.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the predictors could be used to develop an adoption index for safety technologies that practitioners can use as an empirical base for making informed decisions. Readiness index and adoption index have been explored using different methods with varying levels of success in other construction domains (Goodrum et al , 2011; Al Yahya et al , 2018). The authors are currently developing an adaptable adoption index for worker-centric safety technologies (wearable safety device for example) utilizing the findings of the present research.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In addition to cost savings, several studies indicated that top management support plays a big part in the adoption of technologies in the construction industry (Peansupap and Walker, 2005; Gambatese and Hallowell, 2011; Rankin and Luther, 2006). Given the industry’s profound resistance to change, researchers have highlighted the need for emerging technologies to be compatible and interoperate with existing systems (Son et al , 2015; Al Yahya et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though this statement was made more than a decade ago, the adoption rate has not seen any drastic improvement, which further confirms the industry's conservative nature. This scenario is often attributed to the readiness of the sector to adopt EP [62,71,73,74].…”
Section: E-procurement Technology Adoptionmentioning
confidence: 99%
“…Many of the research conducted on both existing procurement paradigms, i.e. EPT and SPP, found implementing the two paradigms independently [34], [35]. This strategy has culminated in a slow rate of adoption of both practices [7], [36] which hinders the ability to promote Eprocurement and sustainable procurement effectively and efficiently.…”
Section: Problem Statementmentioning
confidence: 99%